ANALISIS WORDWALL UNTUK MENINGKATKAN LITERASI IPAS PADA KELAS IV DI SD NEGERI WONOTINGAL SEMARANG - Maulina Rizky Faradine; Ngurah Ayu Myoman Murniati; Bernardus Irianto; Iin Purnmasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
ABSTRACT One of the basic skills that students must have is reading. In elementary school, low reading ability can occur in both lower and upper grades. Wordwall as a tool to help elementary school students master reading skills. The aim of this research is to find out the wordwall to improve science literacy in class IV of the Wonotingal State Elementary School, Semarang. This research method uses qualitative research. The type of research carried out is case study research. This research was carried out in class IV of Wonotingal State Elementary School, Semarang. Learning using a wordwall can train students' reading skills. Apart from that, it can teach students to understand the meaning of words, sentences and texts as a whole, as well as being able to read carefully and look for keywords in questions asked by the teacher via the wordwall. Apart from improving literacy skills, students can also improve their speaking skills. This activity is carried out when the question of money activity is held by the teacher to check the level of understanding of the presentation of the material that has been explained by the teacher previously. Keywords: Wordwall, Literacy, Science